Comparison of active impurity control between lithium and boron powder real-time injection in EAST. (28th September 2021) - Xu, W; Hu, J S; Sun, Z; Maingi, R; Zuo, G Z; Qian, Y Z; Li, C L; Zhang, L; Meng, X C; Huang, M; Gao, W; Duan, Y M; et al.
Abstract: The lithium and boron powder have been successfully real-time injected into Experimental Advanced Superconducting Tokamak (EAST) high-confinement (H−) mode discharges, showing good wall conditioning effects, especially on the impurities control. Both of lithium and boron powder particles are gravitationally accelerated into the upper edge of a upper single null discharge. The lithium powder real-time injection effectively reduced the tungsten impurity content both in the plasma edge and core. Contrary to the lithium injection, the boron injection mainly reduced the impurities content in the plasma core, while the impurities increased in the edge. This mainly due to that there was an edge harmonic mode stimulated by boron injection, providing sufficient particles transport. Moreover, the impurities control through boron injection has much wider operation windows than lithium powder injection. Furthermore, there was accumulative wall conditioning effects after sequential boron powder injection discharges.